The side-to-side differences in bone mineral status and cross-sectional area in radius and ulna in teenage Taiwanese female volleyball players - Chang, C. K.; Lin, H. L.; Tseng, H. F. (Biology of Sport, 2008)
Regular physical training has been shown to affect bone development. It has been shown in Caucasians that athletes participated in sports involving long-term unilateral mechanical loading showed significantly larger dominant-to-nondominant differences in BMC and BMD in humerus and radius than those in sedentary subjects. However, racial differences do exits in bone metabolism and no information was available regarding the effect of unilateral mechanical loading on bone development in teenage Asian females. The differences in bone mineral content (BMC), mineral density (BMD), and cross section area of distal radius and ulna between dominant and non-dominant limbs were investigated in teenage female volleyball players. Thirty-nine volleyball players (VOL group) from junior national team and a high school and thirty gender-, height-, weight- and age-matched sedentary subjects (CON group) were recruited. The bone parameters were measured with a dual-energy X-ray absorptiometry bone densitometer. In VOL group, dominant radius BMC and ulna BMC and cross-sectional area were significantly higher than those of non-dominant hand. In CON group, dominant ulna BMC and cross-sectional area were significantly higher than those of non-dominant hand. All bone parameters measured were significantly higher in VOL group than those in the respective sites in CON group. The percent side-to-side differences were not significantly different in any parameters measured between the 2 groups. This study suggested that long-term regular volleyball training did not result in more significant bilateral difference in BMC, BMD, and cross-sectional area in radius and ulna in Taiwanese teenage females.